From Motivation to Mastery: How Intellectual and Emotional Intelligence Drive Teacher Performance - Happy, Happy; Taslim, Sally Jessica; Chandra, Vanisa; Rosaline, Herlina (Universitas Pamulang, 2025)
The graduation outcomes and character development of students rely significantly on the effectiveness of teachers, both in the classroom and in extracurricular settings. High-performing teachers are more likely to meet instructional targets, whereas low teacher performance can disrupt the teaching process and negatively impact student learning outcomes. A total of 103 respondents were selected through purposive sampling techniques. Data collection was carried out via questionnaires, followed by analyses including descriptive statistics, validity and reliability tests, normality tests, classical assumption tests, and coefficient of determination analysis. The findings reveal that work motivation significantly and positively influences teacher performance. The analysis yielded an adjusted R-square value of 0.495, suggesting that the independent variables—work motivation, intellectual intelligence, and emotional intelligence—together explain 49.5% of the variation in teacher performance, with the remaining 50.5% being influenced by factors outside the scope of this. Additionally, intellectual and emotional intelligence were found to have a positive impact on teacher performance.Implications for School Leadership and Stakeholders The results underscore the importance of school principals serving as role models by exemplifying high work motivation and possessing adequate levels of intellectual and emotional intelligence to inspire and enhance teacher performance. Furthermore, schools are encouraged to implement targeted professional development programs aimed at improving these critical attributes among teachers. Such initiatives might include structured training sessions, mentoring opportunities, and comprehensive support systems to address professional challenges. By fostering a conducive and supportive work environment, these measures can significantly enhance teacher effectiveness and, by extension, educational outcomes.